An Efficient Algorithm for EM Scattering from Anatomically Realistic Human Head Model Using Parallel CG-FFT Method. (24th March 2014) - Zhao, Lei; Chen, Gen
Abstract : An efficient algorithm is proposed to analyze the electromagnetic scattering problem from a high resolution head model with pixel data format. The algorithm is based on parallel technique and the conjugate gradient (CG) method combined with the fast Fourier transform (FFT). Using the parallel CG-FFT method, the proposed algorithm is very efficient and can solve very electrically large-scale problems which cannot be solved using the conventional CG-FFT method in a personal computer. The accuracy of the proposed algorithm is verified by comparing numerical results with analytical Mie-series solutions for dielectric spheres. Numerical experiments have demonstrated that the proposed method has good performance on parallel efficiency.